Credibility of health websites on infectious diseases: Are there any fully trustable website to read on Ebola? - Valizadeh-Haghi, Saeideh; Rahmatizadeh, Shahabedin; Ansari, Masoumeh; Hamzehei, Ronak (Archives of Advances in Biosciences, 2018)
When a new disease develops, people are looking for information about that disease where the internet is considered as one of the sources of health information. Beside empowering individuals to identify and select valid information, reliable and up-to-date websites should also be introduced for them. Therefore, the present study aimed to evaluate and identify the high quality websites on Ebola virus and disease. To do this study, the term "Ebola" was searched for in Google, Yahoo, and Bing search engines using the Google Chrome browser. Three pages were obtained from the search in these three selected search engines and were examined, with the exclusion of duplicate websites, non-English websites, the results related to news, images, ads, and inaccessible websites; finally, 43 websites out of the 90 retrieved websites were selected for evaluation. The research tools included the HONcode toolbar and an eight-item checklist was developed by the researchers based on the HONcode of conducts. The result showed that out of 43 websites evaluated, only 6 websites (14%) were trustable and the 86% were not approved after evaluation based on the HONcode criteria. Only 37% of evaluated websites have been considered complementarity criterion. Justifiability was the most considered criterion and 95% of evaluated websites had paid to distribute information fairly enough. Online information about Ebola is available on many websites and this information affects people’s health decisions and behaviors. Physicians and other health professionals can help patients and other community members to find their needed information on infectious diseases (e.g. on Ebola) from the most reputable and valid international websites.